PENGEMBANGAN MEDIA VIDEO BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA PEMBELAJARAN TEMATIK TERPADU DI KELAS IV SEKOLAH DASAR - Jendriadi; Fauzi, Ahmad (Jurnal Riset Pendidikan Dasar Dan Karakter, 2024)
This study aims to develop an integrated thematic learning media based on video for grade 5 elementary school students. Using the R&D method with the 4D model (define, design, development, dissemination), the dissemination phase involved a trial with ten students. The research instruments included a media validation sheet and questionnaires for the practicality of both teachers and students. The validation results showed that the media was very valid, with scores of 3.75 from the design expert, 3.44 from the content expert, and 3.28 from the language expert, with an overall validation score of 3.49. The practicality score from teachers was 92% (very practical) and from students was 90% (very practical). The effectiveness score was 80% (very effective). In conclusion, the Contextual Teaching and Learning (CTL)-based media for grade 5 elementary school students is highly valid, practical, and effective.